Level of consciousness on church mission of the selected parishes of the Diocese of Greater Manila area : basis in revitalizing the diocesan mission program - Hinay, Medever O. (Quezon City : St. Andrew's Theological Seminary, 2016)
This study determined the level of consciousness of the selected parishes on Church Mission with the end in view of revitalizing the diocesan missionary program.
A thesis presented to the faculty of St. Andrew's Theological Seminary in partial fulfillment of the degree, Master in Divinity, school year 2015-2016.
Thesis (M.Div.)-- St. Andrew's Theological Seminary